Demineralized bone matrix and calcium-phosphate cement in bone regeneration in rats - Silva,Luiz Carlos Ferreira da (2018)
Abstract Purpose: To compare bone regeneration in critical-sized defects in rat calvarium using demineralized bone matrix and calcium phosphate cement. Methods: Thirty Wistar rats were divided into 3 groups of 10 animals each. Two defects of 5-mm were made in the parietal bones of each animal. Group I had calcium phosphate cement placed in the experimental defect, Group II had filled with demineralized bone matrix and Group III had with the combination of the matrix and cement in equal parts. All animals had one defect left unfilled to serve as controls. Five animals in each group were sacrificed at 4 and 8 weeks. Histomorphometric analysis was used to quantify the amount of new bone within the defects. Results: The results showed that demineralized bone matrix-treated defects had significantly more new bone at 4 weeks compared to calcium phosphate cement-treated defects (p=0.03) and also had significantly more new bone at 8 weeks compared to unfilled defects (p=0.04). Conclusions: The demineralized bone matrix was superior to calcium phosphate cement in bone regeneration. It seems that calcium phosphate cement acted by inhibiting the osteogenesis when associated with a demineralized bone matrix and this combination should not be recommended.